DOES MARKET MICROSTRUCTURE MATTER? FOREIGN AND DOMESTIC INSTITUTIONAL OWNERSHIP TO AGENCY COST - Fitri Ismiyanti (Journal of Management and Business, 2008)
This research provides measure of absolute and relative equity agency costs for corporations under different ownership and management structures. Miller (1977) argues that divergence of opinion among investors causes the price difference of the price of a security. The dispute mechanism causes the forming price to be further of closer to its intrinsic value. Greater the divergence of opinion, causes greater the gap between the price and its’ intrinsic value. This study tests a new condition that reflects the existence of agency conflict, which is the conditions of stock price premium and stock price discount and related to agency cost control mechanism through foreign and domestic institutional ownership. The two conditions then called as price spread. This study tests four interrelated hypotheses in conditions of stock price premium and stock price discount that related to agency cost, foreign institutional ownership and domestic institutional ownership. Analysis method employs complete structural equation model (SEM), and multigroup SEM with constrained and unconstrained parameters. The direction of the study results consistent with result prediction. Nevertheless, there is one insignificant relationship, which is domestic institutional ownership towards agency cost. This indicates that the relationship hold but remains statistically unproven.